Goodwill as an accounting category (Economics and region, 2019)
Under modern conditions, the decisive factor for success is the availability of intellectual resources and their effective use in economic activity. Goodwill acts as an important tool to strengthen the competitiveness of a business entity because it provides additional benefits to the enterprise. The article summarizes approaches to the interpretation of the concept of “goodwill”, presented in regulatory legal acts and scientific literature. It is established that both regulatory and scientific sources do not contain a single statement of the concept of “goodwill”. The signs of goodwill are defined with the aim of interpreting this concept.
Keywords: goodwill; recognition; measurement; classification; intangible asset